Numerical simulation for suction detection based on improved model of cardiovascular system. (August 2022) - Wu, Xiangyu; Zhang, Yunpeng; Zheng, Xiangyuan; Liu, Hongtao; Wang, Houfu
Highlights: Improved valve motion model is combined with lumped parameter model of the human cardiovascular system. Hemodynamic simulations of cardiovascular system are achieved under different conditions. The dependence of valves angles on pump speed is investigated. Critical pump speed for the suction phenomenon of LVAD is determined by hemodynamic simulation. Abstract: With the success and increasingly widespread use of left ventricular assist devices (LVAD) in clinical practice, how to make the operating conditions of left ventricular assist devices better adapted to heart failure patients has always been an important topic. In this paper, an improved numerical model was proposed to study the pumping speed of the left heart assist device for heart failure patients when suction occurs. In this paper, an equivalent electrical network modeling approach was used to model the human cardiovascular system. During the modeling of the heart valves, we considered the main factor of the transvalvular pressure difference that affects the motion of the heart valves. Then the controlling equations of valve motion were established and the hemodynamic properties were derived by applying the valve motion resistance model to the lumped parameter model of the human cardiovascular system. With LVAD support, we simulated the degree of heart failure with an ejection fraction of less than 40% and obtained a curve of linear increase of pump flow with pump speed. The results show that the developed model can exhibit several important features that are missing when using the ideal diode valve model. With LVAD support, the simulation results show that suction occurs at 13, 698 r/min and 15, 289 r/min when we use the valve motion model and the ideal diode valve model, respectively. The improvement of the cardiovascular lumped parameter model successfully improved the accuracy of hemodynamic simulations, which is important for improving the quality of life in LVAD-supported heart failure patients.